Effect of Hydrothermal Extraction Temperature on Antioxidant Activity of Phaleria Macrocarpa (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Phaleria macrocarpa, or God's Crown, is a medicinal plant rich in bioactive compounds, including minerals, vitamins, alkaloids, flavonoids, and vincristine (a polyphenol). These compounds have shown potential in treating various ailments such as cancer, diabetes, kidney stones, diarrhoea, and vomiting. This study aimed to optimize the extraction of bioactive compounds, particularly flavonoids and phenols, from P. macrocarpa fruit. Various extraction methods were employed, including hydrothermal extraction at different temperatures, decoction, and maceration. The resulting extracts were analysed for total flavonoid and phenol content and antioxidant activity. Colorimetric methods, using AlCl₃ and Folin-Ciocalteu reagents, were used to determine the respective contents. Antioxidant activity was assessed using the DPPH assay. Hydrothermal extraction at 175°C yielded the highest levels of flavonoids, phenols, and antioxidant activity. However, higher temperatures led to a decrease in these parameters, suggesting that excessive heat can degrade bioactive compounds.